Anti-hydrolysis effect of aromatic carbodiimide in poly(lactic acid)/wood flour composites. (December 2017) - Holcapkova, Pavlina; Stloukal, Petr; Kucharczyk, Pavel; Omastova, Maria; Kovalcik, Adriana
Abstract: Poly(lactic acid) (PLA) filled with wood flour (WF) is more susceptible to hydrolysis compared to pure PLA. This work shows that the hydrolysis reactions leading to chain scission can be hindered by using 2 wt% of bis(2, 6-diisopropylphenyl)carbodiimide (ZIKA). It was found that the addition of ZIKA supports the crosslinking of PLA/WF composite. The crosslinking slightly hindered the annealing efficiency of wood flour and increased the stiffness of biocomposites. The thermal stability of biocomposites containing ZIKA was slightly improved. The relevance of the antihydrolysis effect of ZIKA during melt processing of biocomposites was correlated with the rheological and molar mass properties. The hydrolytic stability of biocomposites was determined under buffer solution conditions at accelerated temperature 80 °C and pH of 7. The determined lower depolymerisation and hydrolysis rates of PLA/WF-ZIKA composites indicate that the service lifespan of biocomposites can be prolonged by the addition of ZIKA additive.